Design and Experimental Validation of an SDR-Based Private LTE Network for Flood Monitoring - Bambang Candra Wibawa; Gunawan Wibisono (International Journal of Electrical, Computer, and Biomedical Engineering, 2026)
The widespread impact of hydrometeorological disasters, such as floods, necessitated a reliable and rapidly deployable communication infrastructure to support real-time monitoring and early warning systems. During such events, conventional public cellular networks frequently collapsed, hindering critical information exchange. To address this vulnerability, the study presented the design and performance validation of a private LTE network based on software-defined radio SDR USRP B210 and open-source software, intended as a resilient backbone for an IoT-based flood monitoring system. The system was tested to assess its signal quality and user experience metrics across varying radial distances. Signal analysis confirmed severe channel degradation, with the SINR dropping from the “Excellent” category at 3 m to the “Fair” and “Poor” category at 9 m. This SINR decline directly caused the downlink throughput to fall drastically from 27 Mbps to a low of 2.8 Mbps and significantly inflated the maximum latency to 87 ms due to frequent HARQ retransmissions. Despite these constraints, the network supported low-bandwidth IoT RSRP logging for modem consistency verification and sustained high-demand services including real-time data communication and voice and video calls. Overall, the results validated the system’s ability to establish resilient and self-sustained connectivity to support disaster mitigation and response operations.